Entangling Alliances : Foreign War Brides and American Soldiers in the Twentieth Century. - Zeiger, Susan, 1959- (NYU Press, 2010)
Throughout the twentieth century, American male soldiers returned home from wars with foreign-born wives in tow, often from allied but at times from enemy nations, resulting in a new, official category of immigrant: the "allied" war bride. These brides began to appear en masse after World War I, peaked after World War II, and persisted through the Korean and Vietnam Wars. GIs also met and married former "enemy" women under conditions of postwar occupation, although at times the US government banned such unions. In this comprehensive, complex history of war brides in 20th-century American histo.